Cyanobacterial Diversity In Selected Tropical And Polar Environments - Abdul Rahman, Nur Fadzliana (2019)
Cyanobacteria are the most ancient and widespread group of photosynthetic prokaryotes and had a major role in the evolution of the plant kingdom and Earth’s atmosphere. They are primary producers in a wide variety of habitats and are able to thrive in harsh environments. This study explored the cyanobacterial communities in sediment and soil samples collected from selected areas from Antarctic (Browning Peninsula, Dee Island, Greenwich Island and Reeve Hill), Arctic (Kvartsitsletta and Polish Polar Station) and Tropical (Air Terjun River, Air Itam River, Dondang River, Jelutong River and Pinang River) regions, by identifying taxa via 16S rRNA gene amplicon sequence data. 16S rRNA gene amplicons generated from 11 samples were sequenced using illumina Miseq, with the targeted V3 and V4 regions yielding approximately 1 million reads per sample. East Antarctica (Browning Peninsula and Reeve Hill) recorded nine genera of cyanobacteria and west Antarctica (Dee Island and Greenwich Island) recorded seven genera. The two Arctic sampling sites recorded the lowest number of genera, five.